Puszcza Białowieska; czym była, czym jest, czym ma być w przyszłości? - Szwagrzyk, Jerzy (Leśne Prace Badawcze, 2016)
For many centuries, management of the Białowieża Forest has not focused on timber production. Therefore, despite hunting, grazing by domestic animals and sporadic cutting of valuable trees the forest has retained its natural character. After World War I, a small part of the Białowieża Forest was protected as a reserve that later became a national park, while the remainder was managed for timber. After World War II, the protection status of the Polish part of the Białowieża Forest was maintained with the national park at the center surrounded by managed stands. During the last few decades, the national park was enlarged and new reserves were established. However, the majority of the Białowieża Forest is still managed for timber. The forest management has been sustainable for decades and in the last few years logging has even been strongly reduced, to a level comparable with some national parks. In recent years the Białowieża Forest, like many areas in Central Europe, has been plagued by a high spruce mortality caused by bark beetles. In managed forests, cutting the infested spruces and removing them from the forest is a standard practice aimed at reducing the growth rate of the bark beetle population. This, however, raises the question of whether we expect the Białowieża Forest to remain a managed forest, in which case the fight against bark beetles would be justified, or whether we want it to be converted into a large national park? In the latter case, cutting trees to fight bark beetles would be inconsistent with the aim of conservation. Recent discussions concerning the Białowieża Forest have been dominated by two different ideologies for nature protection. The first approach aims at protecting nature to make it sustainable, beautiful and healthy. In the second approach, protecting nature is achieved by removing any direct human influence, even if the resulting natural environment does not meet our expectations.